PREFERENSI GENERATOR SIKRON BERBASIS ANALITYCAL NETWORK PROCESS (ANP) UNTUK LABORATORIUM PERMESINAN KAPAL - Sunu Arsy Pratomo; Lilin Hermawati (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2022)
The Government's goal to make Indonesia an Maritime Country must be supported by all elements of society, especially is from the education sector. As one of the maritime education institutions to improve competent human resources in its field, it needs training and supporting facilities and infrastructure. One way to increase competence is to supply cadets with capabilities in the field of operation and maintenance of ship machining. Synchronous generator is one of the important components in ship machining. Therefore, the ability to operate and maintain generators is absolutely necessary for cadets in the world of work. Standard selection of generator in the Shipbuilding Laboratory follows Government standards through the Ministry of Transportation Regulations. To choose the best electricity generator, a special method is needed. The solution to this problem is the use of the Analytical Network Process (ANP) to determine synchronous generators that meet the quality standards and specifications of stakeholders.By implementing ANP, the synchronous generator is obtained according to quality standards with the specifications desired by stakeholders. In applying ANP, weighting is based on criteria, namely: durability, maintenance, spare parts, specifications and price. Then obtained an electric generator with appropriate quality standards and specifications.Results of data processing using the ANP method obtained electical generator alternative selection with each weight is adalah CUMMINS GFS-C30KW 41,6 %, HARTECH HT35Y 33,9 %, and CATERPILLAR C2.2 24,5 %.